2006
DOI: 10.1007/s00774-006-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

Threshold value of serum 25-hydroxyvitamin D concentration in relation to elevated serum parathyroid hormone concentrations in elderly Japanese women

Abstract: This study was designed to determine the threshold value for 25-hydroxyvitamin D [25(OH)D] concentration in relation to elevated serum parathyroid hormone (PTH) concentrations in elderly Japanese women. The subjects were 582 noninstitutionalized, ambulant women who lived in a community in Japan. Serum 25(OH)D concentrations were determined using the Nichols Advantage chemiluminescent assay, and serum intact PTH concentrations were determined with a two-site immunoradiometric assay. Demographic characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Classification of vitamin D sufficiency and insufficiency is typically based on the observance of elevated PTH (20,4547), at or around circulating 25-OH-VitD concentrations of less than 80 nM (30 ng/ml). The higher PTH levels observed with increasing deficiency of 25-OH-VitD in the current study are consistent with previous studies (45,48,49). Interestingly, circulating levels of leptin exhibited a similar pattern, increasing sharply below the deficiency level for 25-OH-VitD.…”
Section: Discussionsupporting
confidence: 93%
“…Classification of vitamin D sufficiency and insufficiency is typically based on the observance of elevated PTH (20,4547), at or around circulating 25-OH-VitD concentrations of less than 80 nM (30 ng/ml). The higher PTH levels observed with increasing deficiency of 25-OH-VitD in the current study are consistent with previous studies (45,48,49). Interestingly, circulating levels of leptin exhibited a similar pattern, increasing sharply below the deficiency level for 25-OH-VitD.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, serum 25(OH)D exhibited positive correlations with BMD values of the lumbar spine (L1-L4) and more significantly with that of neck femur even after adjustment for age and BMI; the latter observations were similar to that observed in other studies in both young [68][69][70][71][72] and elderly [9,73] women. In addition, several studies have demonstrated an inverse correlation between serum PTH levels and BMD, particularly at the femoral neck [44,49,74]; these studies showed that subjects with increased PTH levels in vitamin D insufficiency exhibited lower BMD values and higher bone turnover than subjects with decreased PTH levels.…”
Section: Discussionsupporting
confidence: 88%
“…This study also showed (20,21) or even in healthy subjects (22,23). Up to our best knowledge, there are plenty of studies which found negative correlation between serum PTH and 25(OH) vitamin D level, especially in the range of 10 to 50 ng/ mL (25-125 nmol/L) (24), but only few studies suggested a certain threshold for 25(OH) vitamin D to prevent secondary hyperparathyroidism (25,26), especially in adult patients with CKD (27). Some other studies also found this relation more complex and related to age and ethnicity of CKD patients (28,29).…”
Section: Discussionsupporting
confidence: 54%